PERAN HADIS DALAM ADVERTENSI LAYANAN URUN DANA (CROWFUNDING) SYARIAH PADA AKUN INSTAGRAM SHAFIQ ID - Azis, Fadli Azis Darmansyah (Amsal Al-Qur’an: Jurnal Al-Qur’an dan Hadis, 2025)
Abstract. This research explores the shift in the function of hadith in the use of social media, particularly Instagram, as a promotional tool for Islamic investment by the Shafiq id account. Hadith, initially a source of Islamic law, has now been adapted into a modern marketing instrument to increase company revenue. Hadith content is creatively packaged to support product promotion, influencing readers' responses and assessments. This study covers financial literacy, risk perception, and factors affecting investment interest in the Islamic Capital Market. In the context of Islamic crowdfunding, the research highlights the definition of crowdfunding, particularly Islamic securities crowdfunding (SCF), and its investment instruments, such as sukuk. PT Shafiq Digital Indonesia is introduced as a provider of Islamic crowdfunding services. Analysis of data from Shafiq id's Instagram posts indicates that the use of hadith content does not significantly affect the success of sukuk issuance, which is more influenced by public enthusiasm and investment trends. This study examines the modification of hadith use as an advertising medium for Islamic investment, showing that hadith has been commodified and used as a tool for economic legitimacy, creating a commercial identity within the Islamic investment industry. This research provides insights into the shift in the function of hadith on social media and its impact on religious practices in business and investment contexts. Abstrak. Penelitian ini mengeksplorasi pergeseran fungsi hadis dalam penggunaan media sosial, khususnya Instagram, sebagai alat promosi investasi syariah oleh akun Shafiq id. Hadis, yang awalnya sebagai sumber hukum Islam, kini diadaptasi menjadi instrumen pemasaran modern untuk meningkatkan omset perusahaan. Konten hadis dikemas secara kreatif untuk mendukung promosi produk, memengaruhi respons dan penilaian pembaca. Kajian ini mencakup literasi keuangan, persepsi risiko, serta faktor yang memengaruhi minat investasi di Pasar Modal Syariah. Dalam konteks urun dana syariah, penelitian menyoroti definisi crowdfunding, khususnya securities crowdfunding (SCF) syariah, dan instrumen investasinya seperti sukuk. PT Shafiq Digital Indonesia diperkenalkan sebagai penyedia layanan permodalan urun dana syariah. Analisis data postingan Instagram Shafiq id menunjukkan bahwa penggunaan konten hadis tidak secara signifikan memengaruhi kesuksesan penerbitan sukuk syariah, melainkan lebih dipengaruhi oleh animo masyarakat dan tren investasi. Penelitian ini mengkaji modifikasi penggunaan hadis sebagai media advertensi investasi syariah, menunjukkan bahwa hadis terkomodifikasi dan digunakan sebagai alat legitimasi ekonomi, menciptakan identitas komersial dalam industri investasi syariah. Penelitian ini memberikan wawasan tentang pergeseran fungsi hadis di media sosial dan dampaknya pada praktik agama dalam bisnis dan investasi.